AL AZHAR ZAKAT COLLECTION INSTITUTION'S PUBLIC RELATIONS COMMUNICATION STRATEGY IN INCREASING DONOR PARTICIPATION THROUGH INSTAGRAM SOCIAL MEDIA - Nopen Setiawan; Fahmy Fotaleno; Horidatul Bakiyah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The development of social media has changed the communication patterns of philanthropic organizations in reaching the public. The Al Azhar Zakat Institution (LAZ) utilizes Instagram to strengthen its image and increase donor participation amid challenges of trust and declining fund collection growth. This study aims to analyze the communication strategies implemented by LAZ Al Azhar's Public Relations in increasing donor participation through the Instagram social media platform, as well as identifying the challenges faced and their impact on donor interest. Using a descriptive qualitative method with data collection techniques through in-depth interviews, Instagram content observation, and documentation, the results show that the strategies implemented include targeting a young audience (aged 24–35 years), an edutainment approach, the use of soft selling techniques, and the utilization of social momentum. These findings were examined through the Agenda Setting theory, which emphasizes the role of the media in influencing public perception of important issues such as Zakat, Infak, and Sedekah (ZIS). This study contributes to the development of digital communication strategies for Islamic philanthropic institutions in expanding their reach and increasing donor participation in the social media era.